Kajian Ekologi Perkebunan Jambu Gondang Manis Di Desa Gondang Manis Kabupaten Jombang - Pangesti, Meligia Diage; Yuliana, Anggi Indah; Nasirudin, Mohamad (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
Gondang manis guava is a fruit product of Jombang Regency because of its limited existence in Jombang Regency. The purpose of this study was to determine the ecological conditions in the gondang manis guava plantation in Gondang Manis Village, Jombang Regency. This research was conducted in July – August 2020. This research is descriptive quantitative using a purposive sampling method, namely taking samples directly from the research location with the provision of 5 observation plots from a land area of ​​1500 m2. Observations were made 15 times with an interval of 2 days for 1 month. The observed factors include biotic and abiotic factors. The results showed the average age of gondang manis guava plant was 18 years with an average tree height of 6.5 meters; the average stem diameter is 34.9 cm and the average fruit production is 27.6 kg/tree, the temperature is 29oC, the humidity is 68%, and 11 families of flora and 6 families of fauna are found. The results of soil analysis showed that the soil pH value was neutral (6.6) with very low C-organic conditions (0.62%), very low soil nitrogen (0.00%) and very high soil phosphate (136 ppm).